DETERMINAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KAPANEWON PENGASIH KABUPATEN KULON PROGO DAERAH ISTIMEWA YOGYAKARTA - Novitasari, Rewinka; As ari, Hasim; Bayu Utomo, Rochmad; Wulandari, Ika (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2023)
The purpose of this study was to determine the effect of tax administration, tax authorities service quality, tax socialization, and tax information technology on individual small and medium eterprise taxpayer compliance. The sample in this study used a simple random sampling method, so samples obtained was 100 respondents. Researchers used primary data obtained from distributing questionnnaires to MSME actors in Pengasih Ddistrict. The data analysis technique used is Partial least square (PLS) with the help of the smartPLS application. The results showed that partially the tax administration variable had o effect on individual MSME taxpayer compliance, the tax service quality variable had no effect on individual MSME taxpayer compliance, the tax socialization variable had a significant effect on individual MSME taxpayer compliance, and information technology variables taxation has a significant effect on individual MSME taxpayer compliance.